Pancreatic Carcinoma Masquerading as Groove Pancreatitis: Case Report and Review of Literature - Malde, Deep J; Oliveira-Cunha, Melissa; Smith, Andrew Malvern (JOP. Journal of the Pancreas, 2011)
<!–[if gte mso 9]> Normal 0 14 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Context Groove pancreatitis is a distinct form of chronic pancreatitis affecting the space surrounded by the pancreatic head, duodenum and common bile duct. It is an uncommon pancreatic disease with challenging imaging diagnosis that can lead to surgical dilemmas. The purpose of this study is to report a case and review the current clinical, radiological and pathological characteristics of groove pancreatic carcinoma and groove pancreatitis. Case report A 58-year-old man, with a history of alcohol excess, presented with a 4 month history of upper abdominal pain associated with weight loss and vomiting. Failed duodenal dilatation led to gastroenterostomy with biopsies showing chronic inflammation. Further presentation with jaundice and pancreatic groove mass led to a Whipple’s pancreaticoduodenectomy. Histopathology report demonstrated cystic areas in both medial and lateral walls of his duodenum microscopically consistent with groove pancreatitis and a moderate to poorly differentiated adenocarcinoma. Conclusion Several studies have been attempted to clarify the points of differentiation between carcinoma and pancreatitis in the groove area. This discrimination has been proved to be difficult; frequently the definitive diagnosis is only obtained after surgical intervention. This condition should be considered when making the differential diagnosis in pancreatic groove pathology and duodenal stenosis.